Building Confidence, Competence and Connectivity: An Entrepreneurship Learning Methodology for Women at Risk in Dolly, Surabaya, Indonesia - Antonius Tanan; Siew Mee Barton (International Journal of Small and Medium Enterprises and Business Sustainability, 2015)
It is popular to argue that entrepreneurs are ‘born not made’. There is no question that personality type and innate strengths do play a significant role in equipping individuals to function as entrepreneurs but it is also clear that a lot of the capacity building that can assist somebody in starting their own business, and successfully developing it, involves skills, knowledge and attitudes that can be taught. This paper discusses one model of teaching entrepreneurship that has arisen out of the experience of working with vulnerable individuals who lack specific skills, capital and education. The initial development of this model took place when Ciputra University (UC) began working with women formerly involved in the sex-worker industry in Surabaya’s infamous Dolly neighborhood. These women had very modest levels of formal education, limited life experience, little confidence that they could ever succeed outside the profession that they had known and few skills to facilitate alternative employment. The educational model developed to assist them is broadly applicable to those coming into entrepreneurship with little education or background in business. This model is built around three essential elements, summarised as: Confidence, Competence and Connectedness (‘the 3Cs’). Confidence is built through culinary training for a learning outcome from a psychomotor domain.